Genomic characterization of antimicrobialresistance and virulence factors in Salmonella isolates obtained from pig farms in Antioquia, Colombia - García Álvarez, María Isabel; Vidal, Juana L.; Donado Godoy, Pilar; Smith, Jared; Shariat, Nikki; Valencia, María Fernanda; Gómez Osorio, Luis M.; López Osorio, Sara; Chaparro Gutiérrez, Jenny J. (Public Library of Science, 2025)
Occurrence of antimicrobial-resistant Salmonella strains has been reported worldwide, because of inappropriate use of antimicrobial products in either humans or animals. The presence of multidrug resistant Salmonella in pig production systems had been reported in Antioquia, Colombia. Aim: To identify antimicrobial resistance genes (ARG) in different Salmonella spp. strains isolated from pig productions in Antioquia, Colombia. Methods: Samples were received at the Diagnostic Unit of the Faculty of Agrarian Sciences at the University of Antioquia, from January 1, 2019, to January 2021. A total of 28 isolates of Salmonella spp. were included, which presented phenotypic resistance to more than one antibiotic used in pig farms. Whole genome sequencing (WGS) was performed in the Unit of Genomic of Agrosavia using an automated pipeline from the GHRU- Sanger Institute, employing the Illumina MiSeq platform. Results: WGS revealed 34 ARGs among these isolates. In 25 isolates (89%) more than two ARGs were found. Genes encoding resistance were found for 10 different groups of antibiotics (beta-lactam, aminoglycosides, chloramphenicol, rifampicins, lincosamides, fluoroquinolones, tetracyclines, sulfonamides and trimethoprim). The most frequently observed MDR profile in Typhimurium isolates was AMP-CEX-CEP-CEF-EFT-CEQ-FLU-ENR-TE-FFC-SXT.